A new species of Satyrinae butterfly from Peru (Nymphalidae: Satyrini: Euptychiina) - Huertas, Blanca (Zootaxa, 2011)
A new species of Euptychiina butterfly, Splendeuptychia mercedes n. sp. is described from the Amazonian region and Eastern Andean slopes of Peru. The morphology, distribution and conservation status of the new species are described and discussed.